Primary Care Patients with Drug Use Report Chronic Pain and Self-Medicate with Alcohol and Other Drugs - Alford, Daniel P. (J Gen Intern Med, 2016)
BACKGROUND: Chronic pain is common among patients with drug use disorders. The prevalence of chronic pain and its consequences in primary care patients who use drugs is unknown. OBJECTIVES: To examine: 1) the prevalence of chronic pain and pain-related dysfunction among primary care patients who screen positive for drug use, and 2) the prevalence of substance use to self-medicate chronic pain in this population. DESIGN: This was a cross-sectional analysis. PARTICIPANTS: This study included 589 adult patients who screened positive for any illicit drug use or prescription drug misuse, recruited from an urban, hospital-based primary care practice. MAIN MEASURES: Both pain and pain-related dysfunction were assessed by numeric rating scales, and grouped as: (0) none, (1–3) mild, (4–6) moderate, (7–10) severe. Questions were asked about the use of substances to treat pain. KEY RESULTS: Among 589 participants, chronic pain was reported by 87 % (95 % CI: 84–90 %), with 13 % mild, 24 % moderate and 50 % severe. Pain-related dysfunction was reported by 74 % (95 % CI: 70–78 %), with 15 % mild, 23 % moderate, and 36 % severe. Of the 576 that used illicit drugs (i.e., marijuana, cocaine, and/or heroin), 51 % reported using to treat pain (95 % CI: 47–55 % ). Of the 121 with prescription drug misuse, 81 % (95 % CI: 74–88 %) used to treat pain. Of the 265 participants who reported any heavy drinking in the past 3 months, 38 % (95 % CI: 32–44 %) did so to treat pain compared to 79 % (95 % CI: 68–90 %) of the 57 high-risk alcohol users. CONCLUSIONS: Chronic pain and pain-related dysfunction were the norm for primary care patients who screened positive for drug use, with nearly one-third reporting both severe pain and severe pain-related dysfunction. Many patients using illicit drugs, misusing prescription drugs and using alcohol reported doing so in order to self-medicate their pain. Pain needs to be addressed when patients are counseled about their substance use.